Integrated teaching and learning approach for ESD course - Subki, Noor Syuhadah (Universiti Teknologi MARA, Kedah, 2023)
This article highlights the integrated teaching and learning approach used in learning Education for Sustainable (ESD) courses. The integrated teaching and learning approach by combining online and physical learning tools gives a new and different perspectives of learning process for students through participating in created activities such as synchronize and asynchronized classes, educational gamification, online test, outdoor class reflection, live presentation and many more.